(untitled) (Педагогіка вищої та середньої школи, 2009)
This article is devoted to the issue of communicative competence forming in the context of the professional culture of student-managers in the university. There are given requirements for the manager in the XXI century, requirements for the communicative knowledge and skills. Submitted assumptions for the formation communicative knowledge and skills and expected as a result of the proposed action results.